2002
DOI: 10.1097/00004770-200204000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Leakage of Interim Post and Cores Used During Laboratory Fabrication of Custom Posts

Abstract: The aim of this study was to compare coronal microleakage in two conditions. Twenty-eight extracted upper molars were endodontically treated and divided into two groups and controls: group A: prefabricated post and core permanently cemented; and group B: prepared for a post and restored with a temporary post crown cemented with a temporary cement. The teeth were thermocycled, immersed in black India ink for 1 week, and made transparent. Results indicated that the permanently cemented, prefabricated post and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 8 publications
0
15
0
4
Order By: Relevance
“…The model utilized for this experiment was the one used by Valadares et al [24]. The absence of clouding in the culture medium of the negative control group, and its presence in the samples of the positive control group proved it to be a trustful system, in which the information reproduced objectively the existence or the non-existence of clouding, being the Enterococcus faecalis chosen as the biomarker of this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model utilized for this experiment was the one used by Valadares et al [24]. The absence of clouding in the culture medium of the negative control group, and its presence in the samples of the positive control group proved it to be a trustful system, in which the information reproduced objectively the existence or the non-existence of clouding, being the Enterococcus faecalis chosen as the biomarker of this study.…”
Section: Resultsmentioning
confidence: 99%
“…The test apparatus from the confection of the double chamber experimental model consisted of a structure made of 10 ml glass phials (Wheaton do Brasil S.A., São Bernardo do Campo, Brazil), rubber lids with 20 mm of diameter (Adnaloy Artefatos de Borracha, Ltda, São Paulo, Brazil), and Eppendorf kind of tubes 1,5 ml [24]. In order to grant a proper impermeability, a layer of epoxy resin was applied in the tube-tooth junction, subsequently, a layer of cyanoacrylate was applied on the epoxy resin surface as well as on the root surface, which was made impermeable already, besides, a new layer of nail enamel was used to grant the best possible sealing of the junction tube-teeth and impermeability of the samples.…”
Section: Preparation Of the Test Apparatusmentioning
confidence: 99%
“…Immediate restoration is considered a positive factor to prevent apical recontamination, since the use of definitive cement has better result in relation to apical contamination, compared to temporary cementing [1]. Moreover, teeth prepared to receive pins are at higher risk for apical contamination [11,17].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in literature have assessed the adhesion of intraradicular posts cemented with different cements [12][13][14][15], as well as the fracture resistance of bovine roots restored with different prefabricated posts [16]. Coronal microleakage was assessed by dye ink, comparing posts and cores cemented with permanent and temporary cements, showing that teeth restored with permanent cements had better sealing [17]. Subsequently, using fluid leakage, it was observed that polyethylene fiber and glass fiber posts have less coronal infiltration when compared to stainless steel and zirconia posts [18].…”
Section: Introductionmentioning
confidence: 99%
“…(8) The possibility of endodontic post failure, which may result in loss of retention; the risk of root canal reinfection due to bacterial micro leakage may be due to: stress concentration; and the difference in modulus of elasticity between post and dentin or bond failure of adhesive systems. (17,18) Many investigations have been conducted concerning improvement of the bond strengths between the post and the root canal dentin, including different pretreatment techniques of the post surface. (19)(20)(21)(22) Chemical pretreatment of FRC posts includes silanization (23,24) and etching with hydrofluoric (25) or phosphoric acid.…”
Section: Introductionmentioning
confidence: 99%